Extending shared socioeconomic pathways to future water supply infrastructure scenarios: a case study of San Antonio, TX - Perpetua I Okoye; Ryan A McManamay (Environmental Research Communications)
Municipal water supplies face increasing pressures from aging infrastructure, shortages, and declining quality, necessitating the exploration of alternative infrastructure futures as a critical aspect of addressing potential resource conflicts from growing populations. Multisector and integrated assessment modeling approaches can be used to evaluate alternative Water Supply Infrastructure (WSI) futures and their inherent uncertainties; however, to be compatible with other regional modeling efforts, these approaches first require constructing scenarios that assemble along mitigation and adaptation strategies as localized extensions of Shared Socioeconomic Pathways (SSPs). Here, we build a set of interrelated storyline elements for integrated WSI scenarios as subnational-sectoral extensions of the global SSP storylines that explicitly describe future socioeconomic challenges and tradeoffs. To formally extend subnational SSP narratives to local scales and address socioeconomic tradeoffs among narratives, we developed an indicator framework to explicitly quantify the storyline elements, facilitating a deeper understanding of future scenarios’ synergies and potential tradeoffs in water availability, quality, energy use, and capital and operating monetary costs of treatment and infrastructure development. Upon applying the framework, we found that constraints to meeting future water demands through available surface water supply infrastructure options led to a narrow selection of alternative on-the-ground decisions despite efforts to implement diverse WSI futures. This suggests that current infrastructure decisions and technologies may restrict the diversity of available alternative socioeconomic pathways without major resource use and valuation shifts. These findings can guide future research and policy for infrastructure planning in changing global conditions.